The Millennium Challenge Account : Making U.S. Foreign Assistance More Effective? - Herrling, Sheila; Radelet, Steve (World Bank, 2012)
The U.S. and Germany each undertook a major effort to reform their respective development aid programs. Their paths were different, but both programs incorporate principles present in the AAA. To what extent have these reform efforts succeeded?